Angel Investors and Gender Gap: A Systematic Literature Review - Sara OKLESTKOVA (Communications of International Proceedings, 2023)
Angel investing is an important catalyst for national economic growth, and it is the gender gap that is trending upwards. However, there remain areas that are under-explored. Thus the aim of this paper is to map the current level of knowledge of gender research on the decision-making of angel investors and, based on empirical data, to evaluate the influence of gender on the decision-making of angel investors and identify areas to direct further research on female angels. For this purpose, the methodology of literature search is used, namely secondary analysis and subsequent synthesis of selected scientific articles from the Web of Science database. Scholarly sources are identified based on a combination of relevant keywords, including the use of logical abbreviations. The results show that the core themes of gender gap and angel investing include stereotypes, discrimination, social contact, aversion to risky activities, and fear of failure. In contrast, there is a lack of research in evaluating the impact of gender on the decision-making of angel investors in the conditions of the Czech start-up market, which explicitly implies the need to focus research interest in these areas.
Keywords: Venture capital; business angels; angel capital; female; gender gap